2007
DOI: 10.1111/j.1095-8339.2007.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Perissothallus, a new genus for Late Pennsylvanian–Early Permian noncalcareous algae conventionally assigned to Schizopteris (aphleboid foliage)

Abstract: The morphogenus Schizopteris was established in the early 19th century for late Palaeozoic aphleboid foliage of uncertain affinities, and numerous specimens have subsequently been assigned to this taxon. Some of these fossils do not represent foliage, but rather noncalcareous algae. Although this inconsistency has been noted, an attempt to exclude the algae from Schizopteris has not yet been undertaken. Here we propose the new genus Perissothallus to accommodate those fossils conventionally assigned to Schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…Perissothallus versiformis from the Upper Pennsylvanian of North America and P. densus from the Lower Permian of Germany (Krings et al 2007). Krings et al (2007) used three basic features to distinguish algae from Schizopteris-type aphleboid foliage.…”
Section: Comparisonsmentioning
confidence: 99%
See 4 more Smart Citations
“…Perissothallus versiformis from the Upper Pennsylvanian of North America and P. densus from the Lower Permian of Germany (Krings et al 2007). Krings et al (2007) used three basic features to distinguish algae from Schizopteris-type aphleboid foliage.…”
Section: Comparisonsmentioning
confidence: 99%
“…Barthel (1982), Kerp & Fichter (1985), and Krings et al (2007) suggested that some of the fossils conventionally assigned to Schizopteris do not represent aphleboid foliage, but rather thalli of noncalcareous algae similar in overall morphology to certain extant members of the Chlorophyta (green algae), Phaeophyceae (brown algae), and Rhodophyta (red algae). Krings et al (2007) Krings et al from the Lower Permian of Germany.…”
mentioning
confidence: 99%
See 3 more Smart Citations